ANALISIS LAYANAN WEBSITE TERHADAP KEPUASAN PELANGGAN PADA PT. MODENA INDONESIA DENGAN METODE WEB-QUAL 4.0 - Afrizal, Muhammad; Rizal, Khairul; Ariani, Fattya (Journal of Information System, Applied, Management, Accounting and Research, 2025)
This research aims to assess the service quality of PT Modena Indonesia's e-commerce website using the WebQual 4.0 method, as well as provide recommendations for improving service quality to increase customer satisfaction. This research was conducted as one of the requirements for graduation from the Undergraduate Program (S1) in the Information Technology Study Program at Bina Sarana Informatika University. The methods used include direct observation of the PT Modena Indonesia website, online interviews through distributing questionnaires to customers, as well as literature studies reviewing similar research. The research results show that usability quality, information quality, and service interaction quality have a positive and significant effect on customer satisfaction, both partially and simultaneously. Based on the results of this analysis, it is recommended that PT Modena Indonesia make improvements to these three aspects to increase user satisfaction. This research is expected to help companies optimize their website services and improve the overall customer experience